2002
DOI: 10.1093/protein/15.10.783
|View full text |Cite
|
Sign up to set email alerts
|

A conformational analysis of Walker motif A [GXXXXGKT (S)] in nucleotide-binding and other proteins

Abstract: The sequence GXXXXGKT/S, popularly known as Walker motif A, is widely believed to be the site for binding nucleotides in many proteins. Examination of the crystal structures in the Protein Data Bank showed that about half of the examples having these sequences do not bind or use nucleotides. Data analyses showed 92 different Walker sequences of the variable quartet (XXXX). Ramachandran angles in this segment revealed conformational similarity in the group of 45 proteins, known to bind or utilize nucleotides. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 10 publications
1
80
0
1
Order By: Relevance
“…The Walker A motif is a nucleotide-binding motif that is highly conserved in numerous ATPases 35 . Previous studies revealed that the lysine residue forms a hydrogen bond with oxygen of g-phosphate of ATP and that the serine/threonine residues interact with Mg ion 36,37 . To determine whether TRIM29 has ATP-and ADP-binding abilities, we generated FLAG-TRIM29 WT and a K54A/S55A mutant in which both Lys54 and Ser55 were substituted with Ala. K54A and S55A mutations abrogated the binding of TRIM29 to ATP and ADP (Fig.…”
Section: Trim29 Forms a Protein Complex With Dna Repair Proteinsmentioning
confidence: 99%
“…The Walker A motif is a nucleotide-binding motif that is highly conserved in numerous ATPases 35 . Previous studies revealed that the lysine residue forms a hydrogen bond with oxygen of g-phosphate of ATP and that the serine/threonine residues interact with Mg ion 36,37 . To determine whether TRIM29 has ATP-and ADP-binding abilities, we generated FLAG-TRIM29 WT and a K54A/S55A mutant in which both Lys54 and Ser55 were substituted with Ala. K54A and S55A mutations abrogated the binding of TRIM29 to ATP and ADP (Fig.…”
Section: Trim29 Forms a Protein Complex With Dna Repair Proteinsmentioning
confidence: 99%
“…AtMDN1, like its yeast ortholog, is thus most probably localized in the nucleus. (Ramakrishnan et al 2002). Short consensus sequences are indicated under the alignment.…”
Section: Atmdn1 Sequence Analysismentioning
confidence: 99%
“…A distinguishing feature of the EPKs is a Glycinerich Loop (G-Loop) that lies between the first two beta strands. This is quite distinct from the P-Loop or Walker Motif that is found in hexokinase and other ATPases, where the g-phosphate of ATP is buried under the P-Loop at the base of the cleft that lies between the two lobes (57). In the EPKs the adenine ring of ATP is buried under the G-Loop at the base of the cleft between the N-Lobe and the C-lobe while the g-phosphate is positioned at the edge of the cleft and is more solvent exposed.…”
mentioning
confidence: 74%